Given that a − b = 2 and c − b = 3 , find the value of
a 2 + b 2 + c 2 − a b − b c − a c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Set the equations to a = 2 + b and c = 3 + b and substitute those values of a and b into the equation that we're trying to solve.
Helpful note: a 2 + b 2 + c 2 − a b − c b − a c = ( a + b + c ) 2 − 3 ( a b + b c + a c )
Then all the variables cancel out and left with a number, which is 7
Problem Loading...
Note Loading...
Set Loading...
given: a-b = 2 (i) and c-b = 3 (ii)
c-a = 1 (iii)
then, the given equation is equal to:
[(i)^2 + (ii)^2 + (iii)^2]/2
= [2^2 + 3^2 + 1^2]/2
= {4+9+1]/2
= 7
Final answer: 7